2018
DOI: 10.1186/s13690-018-0277-1
|View full text |Cite
|
Sign up to set email alerts
|

Children who are both wasted and stunted are also underweight and have a high risk of death: a descriptive epidemiology of multiple anthropometric deficits using data from 51 countries

Abstract: BackgroundWasting and stunting are common. They are implicated in the deaths of almost two million children each year and account for over 12% of disability-adjusted life years lost in young children. Wasting and stunting tend to be addressed as separate issues despite evidence of common causality and the fact that children may suffer simultaneously from both conditions (WaSt). Questions remain regarding the risks associated with WaSt, which children are most affected, and how best to reach them.MethodsA datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
227
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(258 citation statements)
references
References 29 publications
19
227
2
Order By: Relevance
“…Following the first ever analysis of aggregate malnutrition (Briend et al 2015;Khara et al, 2017;Myatt et al 2018). The data set out in this paper show there is a clear need to present the full picture of the extent of malnutrition, using a measure like the CIAF, but that it is also important that overlapping groups of malnourished children are not missed; focussing too narrowly, say on just those children who exhibit Wasting and Stunting, which recent analyses estimate a prevalence of around 3% (Khara et al, 2017), may give the impression that serious malnutrition is not very prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the first ever analysis of aggregate malnutrition (Briend et al 2015;Khara et al, 2017;Myatt et al 2018). The data set out in this paper show there is a clear need to present the full picture of the extent of malnutrition, using a measure like the CIAF, but that it is also important that overlapping groups of malnourished children are not missed; focussing too narrowly, say on just those children who exhibit Wasting and Stunting, which recent analyses estimate a prevalence of around 3% (Khara et al, 2017), may give the impression that serious malnutrition is not very prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…(Bergeron & Castleman 2012: 247). The provision of evidence about aggregate and multiple malnutrition is therefore an important contribution (Myatt et al 2018) and this paper aims to articulate the rationale for such measures as well as how to construct these measures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the prevalence of 1.65% obtained in our analysis translates into a quarter-million of under five children affected. These children need particular attention as studies have shown that they are at high risk of dying even when they are moderately wasted [21,46]. Thus, the approach for screening and selecting children for wasting interventions should be adjusted to ensure children with concurrent wasting and stunting are able to access the most effective treatment for their condition.…”
Section: The Concurrence Of Wasting and Stuntingmentioning
confidence: 99%
“…Interventions have sometimes used the sitting height to standing height ratio (or Cormic index) to correct of weight‐for‐height measurements for the body morphology of some ethnic groups (Roberfroid et al, ; Salama et al, ), but the issue of geographical variations body shape requires further study (Briend et al, ). Evolving understandings of the frequency of multiple anthropomorphic deficits and the overlap and dynamic interactions between wasting and stunting will also influence this debate (Myatt et al, ; Wells et al, ). Although it is beyond the scope of this article to adjudicate the debate around MUAC versus WHZ, greater clarity around the specific conditions under which MUAC is an appropriate diagnostic tool, emphasizing its practicality and ease in difficult field situations, will be needed to assuage stakeholders' observed misgivings.…”
Section: Discussionmentioning
confidence: 99%